Impact of working capital management, ownership structure and board size on the profitability of small and medium-sized entities in Nigeria - Tsagem, Muhammad Musa; Aripin, Norhani; Ishak, Rokiah (EconJournals, 2015)
This paper aims to investigate the impact of working capital management (WCM), family ownership and board size on the profitability of small and medium-sized entities in Nigeria.The panel data regression analysis is employed using financial reports of 47 small and medium enterprises (SMEs) of North-West geopolitical zone in Nigerian for the period 2008-2012.The study found a statistically significant relationship between account receivables period, accounts payable period, cash conversion efficiency and board size with SMEs profitability, proxy by gross operating profits.Further, a positive relationship between inventory holding periods, cash conversion cycle and cash ratio with profitability were established.The result suggest that SMEs owners/managers need to give more emphasis to efficient management of their limited resources by managing their account receivables, accounts payable, inventories and cash effectively for improve profitability.In addition, the study contributes to existing literatures on the importance of WCM and board size to SMEs for sustainability and growth.